Fostering Multimodal Literacy Using Powtoon Application in Teaching English Reading - Nurul Mufida; Salim Nabhan (JELITA, 2023)
The 21st century is a digital era marked by the use of technology that can ease human activities including education. Hence, with the existence of technology, students do not only read through textbooks but also other modes of meaning-making including audio, visual, and images. Therefore, this multimodal literacy should be integrated into the teaching and learning process. This study is intended to explore 6 students’ perceptions of using the Powtoon app in fostering multimodal literacy for English reading. This study used a qualitative case study. The data were taken from students of SMP PGRI 1 Buduran, Sidoarjo through interview, observation, and document review. The data were then analyzed using thematic analysis. The data revealed that students perceived several benefits in the form of providing students with the incorporation of multimedia elements into reading materials, assisting students to have better materials understanding, engaging and interactive materials for students through multimodality, and facilitating students in evaluating the multimodal texts.